Design and Validity of E-Modules Based on Cognitive Conflict in Measurement Materials for Grade X Senior High School/Madrasah Aliyah - Zaidida Rahmi; Fatni Mufit (Department of Physics Universitas Negeri Padang, 2025)
Physics education in school often faces challenges due to students’ limited conceptual understanding and persistent misconceptions, particularly in measurement topics. This study aims to develop and evaluate an e-module based on cognitive conflict to address these issues. The research was a development study based on the Plomp model, which includes preliminary research, prototyping, and an assessment phase. The resulting e-module presents a structured learning sequence that activates students’ preconceptions, introduces cognitive conflict, facilitates the discovery of key concepts, and promotes reflection. Designed using Canva Pro and Heyzine Flipbook, that e-module was validated by experts, achieving a high score of 0.95, indicating its suitability in terms of content, visual design, learning structure, and software functionality. The findings suggest that a cognitive conflict-based e-module is an effective tool for enhancing conceptual understanding and reducing misconceptions in the measurement, offering practical value for physics learning in schools.